Exploring Post-COVID-19 Teacher Experiences: Advancing Technology-Driven Professional Development for Contemporary Education - OLUWATOYIN AJANI; Samantha Govender (International Journal of Management, Knowledge and Learning)
Purpose The purpose of this study is to examine the post-COVID-19 experiences of teachers regarding technology-driven professional development activities. It aims to explore the challenges, opportunities, and best practices for equipping teachers with the digital competencies necessary to navigate online and blended learning environments effectively. The study seeks to provide actionable insights for enhancing teacher professional development in the evolving digital landscape of education.